Aliran Informasi Serikat Pekerja Rumah Tangga Tunas Mulia dalam Mensosialisasikan RUU Perlindungan PRT - Anugerah Ayu Sendari; Prismarini Nurdiarti, Rosalia (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2023)
The domestic workers' union (SPRT) acts as a forum for communication between domestic workers (PRT). A series of information exchange processes related to domestic workers took place in this union. One of the important pieces of information on the domestic worker union is the Draft Law on the Protection of Domestic Workers (RUU PPRT). Socialization of the PPRT Bill is needed to support the ratification of this bill into law which has been stalling in the Indonesian Parliament for 19 years. In this process there is a flow of information that allows the socialization of the Domestic Workers Bill to reach all domestic workers. This flow of information is contained in the SPRT Tunas Mulia Yogyakarta. This descriptive qualitative research reveals how and what kind of information flow in the trade unions is in socializing a bill. The case study approach was used in order to provide detailed descriptive data and to assist the socialization of the PPRT Bill as a whole. The theory used in this research is organizational communication theory which discusses the flow of information. The results of the study show that there is a flow of information (message spread, patterns, and directions) within the domestic workers' union when socializing the Domestic Workers Bill. Dissemination of messages occurs simultaneously and sequentially. The pattern of information flow found is a circular pattern, and the direction of information flow is formal (horizontal and vertical) as well as informal. SPRT Tunas Mulia has taken a series of communication approaches to socialize the PPRT Bill. This socialization was carried out so that domestic workers and the public have an understanding of the urgency of ratifying the PPRT Bill. Keywords: Information flow, organizational communication, trade unions, domestic work